MANAJEMEN PROGRAM BIMBINGAN DAN KONSELING PADA SMK DKI JAKARTA - Fauzi Nur Ilahi; Gantina Komalasari; Dede Rahmat Hidayat (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2019)
The results of the guidance and counseling program audit also need to be socialized so that the program runs well and gets encouragement from other teacher personnel. To establish a quality guidance and counseling service program there needs to be a foundation or basis for formulating a program that fits the needs of students, so it is necessary to have stages of planning, dissemination of student needs, and program audits before being implemented to determine the extent to which the program has been implemented and be attained. The method used in this study is quantitative descriptive with the type of survey. The survey method is intended to obtain data from the description of the implementation of a guidance and counseling management system in State Vocational Schools in Jakarta City in particular. Out of the three schools audited the results of the programs carried out by Jakarta Vocational High Schools 6, Jakarta Vocational High Schools 29, and Jakarta Vocational High SchoolsÂ 41 not running optimally